Barley Malting: Potential for Development of Weaning Food in Nepal - Ojha, Pravin; Poudel, Pradeep Kaji; Shrestha, Alok (Journal of Food Science and Technology Nepal, 2022)
The paper aims to review the potentiality of malted barley for the development of weaning food in developing countries like Nepal. Cereals and legumes are mixed to develop weaning food, but the processing step is limited to roasting. Malting activates the enzyme, that converts the complex compound into a simpler form, making it more digestible. Despite commercial baby foods based on malt are imported, utilization of locally available barley is hardly converted to malt and processed to industry. Utilization of malted barley with a proper proportion of legumes, with some fruit, can fulfil the recommended daily allowance of nutrients for weaning children and could be the prospective business in Nepal, if processed hygienically.